Endoscopic Flexor Hallucis Longus Transfer With Interference Screw and Additional Tension Slide Cortical Button for Chronic Achilles Tendon Rupture - Ayla Claire Newton MBBS(Hons), MA(Cantab), MRCS; Samuel Franklin MBBCh(Hons), MRCS; Thomas Lorchan Lewis MBChB(Hons), BSc(Hons), MFSTEd, FRCS(Tr&Orth); Sanjana Mehrotra; Siddhartha Murhekar MBBS, MRCS; Vikramman Vignaraja MBBS, BSc(Hons); Robbie Ray MBChB, ChM(T&O), FRCSed(Tr&Orth), FEBOT (Foot & Ankle Orthopaedics)
Background Endoscopic flexor hallucis longus (FHL) tendon transfer can be used in the management of acute or chronic Achilles tendon rupture (ATR), including in elite sportspeople. A recent cadaveric study demonstrated that an increased ultimate load could be applied using an FHL tendon transfer with interference screw and cortical button applied using a tension slide technique compared with interference screw alone. The aim of this study was to explore patient-reported functional outcomes following this modification to this operation. Methods We reviewed the imaging, history, patient-related outcome measures (PROMs), and complications of 17 patients who underwent endoscopic FHL tendon transfer for chronic ATR using the modified FHL reconstruction technique. The primary outcome was the Manchester-Oxford Foot Questionnaire (MOxFQ), EuroQol–5 Dimensions (EQ-5D), and visual analog score for pain (VAS-Pain) with a mean follow up of 1.5 years. Results Seventeen patients (11 male, 6 female) underwent endoscopic FHL tendon transfer for chronic ATR between September 2020 and May 2023. Mean (SD) age at the time of surgery was 58.3 (16.1) years, and mean (SD) BMI was 27.6 (4.8). A specific event in the history associated with the rupture was present in 13 of 17 patients (76.5%); the median (IQR) time between injury and surgery was 33 weeks (21-42). Sixteen surgeries were primary procedures for chronic ATR, and 1 surgery was a revision procedure after a failed open acute ATR repair. MOxFQ, EQ-5D, and VAS-pain scores all showed a statistically significant improvement postoperatively (minimum 10 months) when compared to preoperative scores. There was 1 symptomatic complication of tibial neuritis (5.9%). Conclusion Endoscopic FHL tendon transfer for chronic ATR augmented using a cortical button as well as an interference screw seems to be a safe and effective procedure, with patients reporting a statistically significant improvement in health-related quality of life, pain, and specific foot and ankle outcome function. Level of Evidence: Level IV, case series.